Burnout Risk Analysis and Job Satisfaction in a Costa Rican Pediatric Hemato-Oncology Department - Cubero González, Osvaldo (2023)
Burnout is a syndrome composed of emotional exhaustion, depersonalization and feelings of low personal achievement, a consequence of an excessive demand for resources at work and a loss of resources to cope with such demand. Burnout affects more professions that require direct contact with people, such as oncology nursing, which in turn could be affecting job satisfaction. The study aims to describe the relationship between the risk of burnout syndrome and job satisfaction in the nursing staff of the Hemato-Oncology Department of a Costa Rican pediatric hospital. The descriptive, correlational, group case study, had a population of 30 people who had been working in this department for more than one year. Data collection was by means of the Maslach Burnout Inventory and the Satisfaction Questionnaire S10/12. The data were analyzed using descriptive statistics and Pearson's correlation. The results of burnout risk indicated that emotional exhaustion had high risk, depersonalization moderate risk and personal accomplishment low risk. Regarding job satisfaction, the averages for physical environment, supervision and benefits received reflect that people consider these aspects as indifferent. No correlation was observed between burnout risk and job satisfaction; however, associations were found between emotional exhaustion and satisfaction with the physical environment and benefits received; depersonalization with satisfaction with supervision; and personal fulfillment with satisfaction with the physical environment and supervision. The relationship between burnout risk and job satisfaction is important because high levels of personal accomplishment could mitigate the adverse effects of emotional exhaustion and may protect staff from suffering from the syndrome and influence the improvement of job satisfaction.